SISTEM INFORMASI SURAT KETERANGAN PENDAMPING IJAZAH (SKPI) BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK CODEIGNITER DI UNIVERSITAS KATOLIK WIDYA KARYA MALANG - Yolandita; R Rahardian; Fery Satria Kristianto (Journal of Information System and E-business, 2023)
The existence of a Diploma Companion Letter at the Widya Karya Catholic University of Malang is a new policy that has been implemented, in which the Head of Study Program is working on it manually, namely collecting scans of student activity documents such as certificates or charters and typing them in using an office application one by one. This becomes a very time-consuming activity because there are many student activities that must be typed and are very prone to errors. The author designed and built a website-based diploma companion letter information system to facilitate the management of these data where from the analysis results obtained four user actors namely students, study program heads, translators, and guardian lecturers. Interaction with the system produces student activity certificate data input activities, data validation activities, data validation activities, and translating activities into English. The making of the program has produced a website-based information system with an easy-to-use user interface with an attractive appearance and is able to speed up the process of inputting student activity data and simplifying the flow of managing diploma accompanying certificate data. In addition, the system also automatically generates the document format for the required diploma companion certificate.